Organizational culture of selected hospitals of Tehran city - Mobin Sokhanvar; Alimohammad Mosadeghrad (Tehran University of Medical Sciences, 2017)
Background: Organizational culture has a crucial role in hospitals' productivity. The success or failure of strategies and plans in organisational change depend on organizational culture. This study aimed to examine the organizational culture of Tehran hospitals in 2014. Material  and Methods: This descriptive-analytical study was carried out in 18 hospitals (public, private and semi-public hospitals) that were selected out of 114 hospitals of Tehran using quota- randomized sampling method. About 696 employees in diagnostic, curative, administrative and logistic departments participated in the study. Data was collected through a valid and reliable questionnaire and analyzed using SPSS20. Spearman, U Man- Whitney and Kruskal- Wallis statistical tests were applied. Results: The mean score of organizational culture was 3.62 out of 6 (moderate). There was a significant relationship between organizational culture and the type of hospitals (p=0.002). The mean score of organizational culture was higher in Private and Semi-public ecurity hospitals respectivey. Attention to details and customer orientation dimensions were high in public and semi-public hospitals and private hospitals respectively. The most and the least mean score of organizational culture was related to administrative and support services units.  Conclusion: Organization culture was evaluated in moderate status in hospitals of Tehran city. Thus, it is recommended  that hospital managers  improve hospitals chr('39')organizational culture  specially in creativity, innovation, integration and teamwork dimensions using organizational engineering culture plans.